Domokos Teleki, der erste Präsident der Societal für die Gesammte Mineralogie zu Jena - Viczián István; Deé Nagy Anikó (University of Szeged, Department of Mineralogy, Geochemistry and Petrology Szeged, 1997)
Count DOMOKOS TELEKI was born 1773 in Sáromberke, Transylvania and died 1798 in Marosvá ;árhcly in age of 25 years. His father was SÁMUEL TELEKI, later Chancellor of Transylvania in Vienna, famous philologist and founder of a Library. He studied in the Vienna University and later became justice of the Royai Court in Marosvásárhely. He was well educated in mineralogy and developed a remarkable mineralogical collection which is today preserved in the TELEKI Library, Marosvásárhely (Tárgu Mure?, Romania). He travelled much in Hungary, Croatia, Bohemia and Germany. On his tour to Germany, he visited professor LENZ in Jena in autumn 1795. In 1797 a Mineralogical Society was founded in Jena and DOMOKOS TELEKI was elected for first president. He could fulfil his office for only less than one year because he died prematurely in 1798. He donated minerals and books the Society, proposed new members and reported on new discoveries. His memory was preserved by the father and by the Society.
Keywords: Természettudományok; Föld- és kapcsolódó környezettudományok